Editorial Enletawa Journal 10.2 - Romero Archila, Yuranny Marcela (Universidad Pedagógica y Tecnológica de Colombia, 2018)
This new edition of ENLETAWA JOURNAL includes articles on how communication is carried out in the EFL classroom, as well as the use of literature to foster foreign language learning. Additionally, we have included a special section on creative writing at the end. This segment is an enticing complement to this volume, and it provides a space in which the author shares one of his historical fiction stories with the community.